MANAJEMEN PROGRAM PENDIDIKAN ANAK USIA DINI DI TK ISLAM IMPIAN YAYASAN SMART HOME KOTA MAKASSAR - Marzuki, Kartini; Latif, Ali (JAPPA: Jurnal Andragogi Pedagogi dan Pemberdayaan Masyarakat, 2024)
This research aims to determine the management of early childhood education programs in the Islam Impian Kindergarten Foundation Smart Home Makassar City. This research uses a qualitative research approach with a case study type of research, the subjects of this research are teachers and principals of the Islam Impian Kindergarten. Data collection was carried out using observation, interviews and documentation methods. The techniques used in data analysis are data reduction, data presentation, and drawing conclusions. Testing the validity of research data was carried out using triangulation of sources and methods. The results of the research show that the management of the early childhood education programs in the Islam Impian Kindergarten Foundation Smart Home Makassar City, in this case the Dream Islamic Kindergarten, in the management process consists of planning, organizing, implementing and supervising. The results of research on (1) planning show that managers prepare and develop the school's vision, mission and goals. After that, determine the activities and programs that will be carried out, and prepare adequate facilities and infrastructure so that these activities can be carried out well. Stage (2) organizing shows that the division of tasks and responsibilities is structured in the school organizational structure. Furthermore, in (3) the implementation of school principals and teachers makes efforts to implement school programs and activities. However, there are programs and activities that cannot be implemented because there are obstacles, namely insufficient funds. And in stage (4) supervision is carried out by the school principal who monitors the teacher's performance so that they can carry out their duties and responsibilities. And look for solutions to the obstacles faced in implementing activities at school.